Work-related psychosocial hazards among emergency medical responders (EMRS) in Mansoura city - Eman Omar Khashaba; Mona Abdel Fattah El-Sherif; Adel Al-Wehedy Ibrahim; Mostafa Ahmed Neatmatallah (Wolters Kluwer Medknow Publications, 2014)
Purpose: This research was done to assess levels of psychosocial stress and related hazards [(burnout, depression, and posttraumatic stress disorder (PTSD)] among emergency medical responders (EMRs). Materials and Methods: A comparative cross-sectional study was conducted upon (140) EMRs and a comparative group composed of (140) nonemergency workers. The groups studied were subjected to semistructured questionnaire including demographic data, survey for job stressors, Maslach burn out inventory (MBI), Beck depression inventory (BDI), and Davidson Trauma scale for PTSD. Results: The most severe acute stressors among EMRs were dealing with traumatic events (88.57%), followed by dealing with serious accidents (87.8%) and young victims (87.14%). Chronic stressors were more commonly reported among EMRs with statistically significant differences (P < 0.05) except for social support with colleagues and supervisors. EMRs had statistically significant higher levels of emotional exhaustion (EE) (20%) and depersonalization (DP) (9.3%) compared with comparative group (4.3%, 1.4% respectively). Also, there was no statistically significant difference between two groups as regards lower personal achievement or depression symptoms (P > 0.05). There was increased risk of PTSD for those who had higher stress levels from death of colleagues [odds ratio (OR) [95% confidence interval (CI)] = 2.2 (0.7-7.6), exposure to verbal or physical assault OR (95% CI) = 1.6 (0.5-4.4) and dealing with psychiatric OR (95% CI) 1.4 (0.53.7) (P > 0.05) Conclusion: EMRs group had more frequent exposure to both acute and chronic work-related stressors than comparative group. Also, EMRs had higher levels of EE, DP, and PTSD compared with comparative group. EMRs are in need for stress management program for prevention these of stress related hazards on health and work performance.